EXISTENCE OF MARRIAGE IN THE SASAK TRIBE IN LOMBOK (MERARIQ) WITHIN THE ESTUARY OF LEGAL PLURALISM - Wahyu Lukman (Jurnal IUS Kajian Hukum dan Keadilan, 2014)
Man is basically a creature of God who has relation (through worship) to God (fardhu a’in) and relation to other creatures as social beings (fard kifayah). This dual relationship will as consequence make a various instruments of what-the-so-called Legal Pluralism. The Legal Pluralism in human life is a bind positioning the human to commit with what are contained in each instrument, even though the instruments are mostly abstract and are only dialectical symbols that have a strong energy leading the physical nd spiritual side of human to obey the God and to do anything on behalf of the “theological and Social Faith” in order to obtain the physical and spiritual peace. To achieve those needs , human his life as a creature implement the legal pluralism, which is believed to serve as an investment in order that his dual function of creation remain maintained and qualified. The instance of this is the implementation of legal pluralism in the procession of “Merariq” (Marriage) in indigenous people the Lombok Sasak tribe. In that procession, three laws are implemented; religious teaching, traditional law, and State law all of which are integratedly applied in the process (3 in 1). Keywords : Existence, Legal Pluralism, Merariq